Potential relationship between gut microbiota and animal diarrhea: a systematic review - Zhang, Yuxin; Ma, Yonggui; Qi, Youchao (Frontiers in Microbiology, 2025)
Diarrhea poses a significant challenge to the growth of the livestock industry by decreasing the productivity and increasing mortality rates in animals. Several factors such as bacteria, viruses, parasites, and stress have been identified as potential contributors to diarrhea. The gut microbiota, a complex micro-ecosystem consisting of trillions of microorganisms such as bacteria, fungi, and viruses, plays a key role in host metabolism, immunity, and nutrient absorption. The gut microbial homeostasis is essential for the intestine to perform physiological functions that maintain the host health. Conversely, gut microbial dysbiosis can lead to the development of various diseases. Recent research has highlighted that gut microbial dysbiosis is a driving factor in the animal diarrhea. Consequently, maintaining the gut microbial homeostasis has become a key focus for the prevention and treatment of diarrhea. This review examines the composition, metabolites and functions of gut microbiota as well as the causes of diarrhea and the alterations in gut microbiota during diarrhea. Furthermore, this review provides insights for future research in this field, especially for alleviating animal diarrhea from gut microbial perspective.